A history of violence: Insights into post-accretionary heating in carbonaceous chondrites from volatile element abundances, Zn isotopes and water contents. (1st January 2018) - Mahan, Brandon; Moynier, Frédéric; Beck, Pierre; Pringle, Emily A.; Siebert, Julien
Abstract: Carbonaceous chondrites (CCs) may have been the carriers of water, volatile and moderately volatile elements to Earth. Investigating the abundances of these elements, their relative volatility, and isotopes of state-change tracer elements such as Zn, and linking these observations to water contents, provide vital information on the processes that govern the abundances and isotopic signatures of these species in CCs and other planetary bodies. Here we report Zn isotopic data for 28 CCs (20 CM, 6 CR, 1 C2-ung, and 1 CV3), as well as trace element data for Zn, In, Sn, Tl, Pb, and Bi in 16 samples (8 CM, 6 CR, 1 C2-ung, and 1 CV3), that display a range of elemental abundances from case-normative to intensely depleted. We use these data, water content data from literature and Zn isotopes to investigate volatile depletions and to discern between closed and open system heating. Trace element data have been used to construct relative volatility scales among the elements for the CM and CR chondrites. From least volatile to most, the scale in CM chondrites is Pb-Sn-Bi-In-Zn-Tl, and for CR chondrites it is Tl-Zn-Sn-Pb-Bi-In. These observations suggest that heated CM and CR chondrites underwent volatile loss under different conditions to one another and to that of the solar nebula, e.g. differing oxygen fugacities. Furthermore, the most water and volatile depleted samples are highly enriched in the heavy isotopes of Zn. Taken together, these lines of evidence strongly indicate that heated CM and CR chondrites incurred open system heating, stripping them of water and volatiles concomitantly, during post-accretionary shock impact(s).